The Determinants of Territorial Well-Being: Proposal for A Research Framework for The City of Tangier - Mariam HARRAS; Mostafa ABAKOUY (Communications of International Proceedings, 2024)
In Morocco, since the announcement of the advanced regionalization project in 2011, improving the attractiveness of territories has become a priority for local authorities who must attract investors and residents, and retain them. The determinants of territorial attractiveness broaden from functional and material considerations to elements of well-being, quality of life, emotions and identity; hence the interest in looking at the notion of territorial well-being. It is a multidimensional concept, and its measurement is a complex exercise, but necessary in the case of the city of Tangier which has become the second economic center of the country and continues to grow. The last study on well-being in Tangier dates back to 2016, and it seemed interesting to us to look into this subject to understand the effect of the city's expansion on the well-being of Tangier residents, and thus highlight the positive points of the Tangier territorial offer, but also what can be improved. The objective of this paper is firstly to understand the concept of territorial well-being through a theoretical approach, and secondly to propose a qualitative research framework that should allow us to understand what are the determinants of territorial well-being in Tangier. For this, we drew inspiration from the results of our bibliographical research.
Keywords: : Territorial attractiveness – Quality of life - Territorial well-being - Tangier